A review of defect engineering, ion implantation, and nanofabrication using the helium ion microscope - Allen, Frances I. (Beilstein Journal of Nanotechnology, 2021)
The helium ion microscope has emerged as a multifaceted instrument enabling a broad range of applications beyond imaging in which the finely focused helium ion beam is used for a variety of defect engineering, ion implantation, and nanofabrication tasks. Operation of the ion source with neon has extended the reach of this technology even further. This paper reviews the materials modification research that has been enabled by the helium ion microscope since its commercialization in 2007, ranging from fundamental studies of beam–sample effects, to the prototyping of new devices with features in the sub-10 nm domain.
Keywords: defect engineering; focused helium ion beam-induced deposition; focused helium ion beam milling; helium ion beam lithography; helium ion implantation